Debunking Lien Myths: Empirical Evidence for an Essential Tool in the Fight against Wage Theft - McBride, Justin; Adler, Laura (Relations industrielles / Industrial Relations, 2022)
SummaryWage lien laws have immense potential to help workers collect owed wages. Because liens can secure rights to property before full adjudication, workers can rest assured that real assets will exist should they prevail and scofflaw employers cannot easily hide assets from collections. Despite the proven usefulness of wage lien laws, opponents frequently argue that broad lien regimes would restrict credit.We use a difference in differences regression analysis to test this argument, using data from the US Small Business Administration 7(a) loan program. We look to two multistate metropolitan areas in the United States with divided wage lien regimes – Chicago and Washington DC. In each case, wage lien laws are permitted in one state (Wisconsin and Maryland, respectively) and not allowed in others (Illinois and Indiana for Chicago, Virginia for Washington).We test the argument against wage liens through regression analysis, looking at gross approvals and interest rates as a reflection of risk. We also aggregate observations by 4-digit NAICS code, by lending institution, and by ZIP postal code and reran regression analyses. The wage lien law treatment did not lower the gross approval amount of 7(a) loans in either market, and did not increase the interest rate faced by borrowers. Indeed, results, while mostly statistically insignificant, in some cases showed the opposite effect. Although these tests do not definitively prove that wage lien laws do not constrict credit flows to small businesses, they provide absolutely no evidence to support such an argument either. The findings thus support the position of advocates supporting wage lien laws as a common-sense tool in the arsenal against wage theft, while casting substantial doubt on oppositional claims against wage liens.AbstractThis article evaluates the impact on business access to credit of wage lien laws, which are an important tool for low-wage workers to reduce wage theft. Worker advocates have tried to expand access to wage liens. Opponents argue that wage liens negatively impact business access to credit. Using data from the Small Business Administration 7(a) loan program, one of the only detailed sources of business loan data, we assess whether lien laws affect business access to credit in two states—Wisconsin and Maryland—using a difference-in-differences framework. We find no evidence to support wage lien opponents’ claims that lien laws reduce credit access. The findings contribute to the understanding of wage liens and provide evidence in support of policies that protect workers.